The compassionate decision-maker - A. Glass (Law Text Culture, 1997)
At times we respond to the predicament of another person with compassion. We come to an understanding of their difficulties and feel for them and suffer with them. Feelings of compassion call for an 'imaginative dwelling' on the particular circumstances of another. We will not have this experience or it will be misdirected if we do not treat the other person as an identifiable individual; someone with a particular history; someone with particular needs and desires. Compassion, in short, calls for particularity. The administration of the law, in contrast, calls for abstraction, it encourages an approach which treats people in general terms. Law's emphasis is on generality and the sameness of people; for justice demands that rights and obligations be applied equally, often irrespective of particular circumstances. That judges settle disputes according to law (and not moral principles or feelings) and that bureaucrats administer without affection or illwill are regulative ideals of our legal and administrative structures.